Identification of Potential Sectors for Tolitoli Regency in the Period 2019-2023 - Aurelie, Eko Putra; Lutfi, Muhtar; Sading, Yunus; Jaya, Andi Herman; Nasruddin, M. Anwar (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The objective of this research is to examine the primary industries that could drive economic development in Tolitoli Regency during 2019-2023. Through the application of Location Quotient (LQ) and Shift-Share Analysis (SSA), this study investigates the competitive strengths of key sectors and their patterns of growth. LQ is utilised to pinpoint the industries that are most prevalent in the region, while SSA evaluates the impact of each sector on changes in Regional Domestic Product (RDP). The findings of the analysis shed light that the Agriculture, Forestry, and Fisheries sector, as well as the Information and Communication sector, display significant LQ scores of 2.09 and 1.89, indicating robust local comparative advantages. These sectors show better growth compared to the national average, despite some local challenges. Conversely, the Mining and Quarrying and Manufacturing sectors show low LQs and are declining, both nationally and locally. These finding reveal a portrait of the sectors that require more attention in terms of policies supporting infrastructure development, technology, and human resource capacity to enhance local competitiveness. This study is expected to enhance regional economic policies by employing data-driven strategies to identify key sectors with the potential to support long-term economic development.